Optimization of multiplex PCR composition to screen for SARS-CoV-2 variants of concern - Maya Savira; Enikarmila Asni; Rahmat Azhari Kemal (Acta Biochimica Indonesiana, 2021)
Background: The ongoing COVID-19 pandemic has led to the emergence of several variants of concern. To rapidly identify those variants, screening samples for whole-genome sequencing (WGS) prioritization could be performed. Objective: We optimized the polymerase chain reaction (PCR) screening method to identify the mutation in spike and ORF1a regions. Methods: We adopted primers targeting mutation in spike and ORF1a region from another study. We optimized the PCR screening method using kits readily available in Indonesia. Firstly, we compared N1 and N2 primers as internal positive control. We also compared GoTaq® 1-Step RT-qPCR System and Indonesia TFRIC-19 BioCOV-19 for the multiplex reaction. We used the optimized composition to screen SARS-CoV-2 positive samples from April – June 2021. Samples with spike and/or ORF1a target failure were subjected to whole genome sequencing (WGS). Results: The results demonstrated the N2 BioCOV-19 reaction as the optimized multiplex PCR composition for spike and ORF1a mutations screening. Whole-genome sequencing has shown that a sample with spike and ORF1a targets failure to be Alpha variant, while other samples with single target failure as non-variants of concern. Therefore, a multiplex RT-PCR composition has been optimized to detect mutation in spike and ORF1a regions. Conclusion: We have optimized a multiplex RT-PCR composition to detect mutation in spike and ORF1a regions.